Implementasi Permainan Angklung Untuk Meningkatkan Kerjasama Anak dan Pelestarian Budaya Lokal di TK ABA 54 Semarang - Anggreini, Lidya Lailatul; Muslam (PAUDIA: Jurnal Penelitian dalam Bidang Pendidikan Anak Usia Dini, 2025)
The importance of developing cooperation and preserving local culture in early childhood is one of the focuses in early childhood education. One of the efforts made by TK ABA 54 Semarang is through angklung games, which are extracurricular activities that combine these two aspects. The problem raised in this study is the importance of developing social skills, especially cooperation, in early childhood, as well as efforts to preserve local culture in the context of early childhood education. This study aims to understand children's cooperation in preserving local culture through angklung games in Group B TK ABA 54 Semarang. This study used a qualitative approach with a descriptive design, involving 23 children aged 5-6 years as research subjects, as well as teachers as additional informants to gain a broader perspective. Data were collected through interviews, documentation and observation techniques. Data analysis was done descriptively by describing the findings. The results showed that angklung games can develop children's social skills, especially in terms of cooperation, as well as introduce and preserve local culture. The implications of this research are important for AUD education, as it shows the crucial role of educators in providing the right tools to develop children's social skills, as well as the importance of readiness of facilities and educators in carrying out learning activities that develop children's social skills.